Clinical manifestation of pediatric mediastinal tumors, a single center experience. Issue 32 (August 2019) - Chen, Chieh-Ho; Wu, Kang-Hsi; Chao, Yu-Hua; Weng, De-Fu; Chang, Jeng-Sheng; Lin, Chien-Heng
Abstract : Abstract: Medical decisions should be well-planned to improve prognosis and reduce complications of mediastinal tumors. In this study, we analyzed the clinical presentations of pediatric mediastinal tumors and their correlation with long-term clinical outcome. Forty patients under 18 years of age diagnosed with mediastinal tumors at China Medical University Children's Hospital between 2001 and 2016 were enrolled. The patients' sex, age of onset, initial clinical symptoms, and treatment outcomes were analyzed. 75% of the patients with mediastinal tumors in this study were men, and the median age of onset was 13 years old (age range: 0–17 years). The overall mortality rate was 40%. The most common tumors were lymphoma (47.5%), followed by germ cell tumors (12.5%), neuroblastoma (12.5%), and thymoma (7.5%). Neuroblastoma was more prevalent in girls younger than 5 years old. The initial presentations of these patients included breathing difficulty (65%), productive cough (47.5%), pleural effusion (54.5%), superior vena cava (SVC) syndrome (35%), neck mass (35%), airway compression (32.5%), fever (30%), chest pain (27.5%), and pericardial effusion (25%). Lymphomas were more likely to be accompanied by neck mass (52.6% vs19.0%, P  = .04) and SVC syndrome (52.6% vs 19.0%, P  = .026), yet also had a better 1-year-survival rate (68.4% vs 52.4%, P  = .02). Overall, lymphoma should be suspected when children present with neck mass and SVC syndrome. Neuroblastoma with a posterior mediastinal origin should be suspected among children younger than 5 years old. Tumor-related airway obstruction, pleural effusion, and pericardial effusion were leading cause of cardiopulmonary instability during sedation for invasive procedures, which should be managed cautiously.